(untitled) (Journal of the College of Basic Education, 2024)
The impact of economic and oil policies in Iraq is one of the topics of all in macroeconomic analysis, and oil policy played an important role in supporting government curricula before 1952, before clarifying the profit-sharing agreement. If oil revenues change, the main financier of Iraq’s budget. And financing the various economic sectors